2020
DOI: 10.1101/2020.08.13.250399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blocking palmitoylation ofToxoplasma gondiimyosin light chain 1 disrupts glideosome composition but has little impact on parasite motility

Abstract: Toxoplasma gondii is a widespread apicomplexan parasite that causes severe disease in immunocompromised individuals and the developing fetus. Like other apicomplexans, T. gondii uses an unusual form of gliding motility to invade cells of its hosts and to disseminate throughout the body during infection. It is well established that a myosin-based motor consisting of a Class XIVa heavy chain (TgMyoA) and two light chains (TgMLC1 and TgELC1/2) plays an important role in parasite motility. The ability of the motor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
(122 reference statements)
1
2
0
Order By: Relevance
“…This would suggest that palmitoylation only partially contributes to concavin function and could hint towards the presence of other protein-protein interaction that are essential for concavin functionality and sporozoite shape maintenance. This finding of partial impact of palmitoylation is reminiscent of the recent work on palmitoylation of the myosin light chain in Toxoplasma gondii (Rompikuntal et al, 2020), where disruption of palmitoylation led to the partial disassembly of the gliding motor complex but had little impact on motility itself. Considering the EM images showing large invaginations of the IMC away from the plasma membrane in concavin(-) sporozoites, we postulate that concavin might contribute towards riveting the plasma membrane to the subtending IMC, which are a constant distance of 25 nm apart.…”
Section: Discussionsupporting
confidence: 61%
“…This would suggest that palmitoylation only partially contributes to concavin function and could hint towards the presence of other protein-protein interaction that are essential for concavin functionality and sporozoite shape maintenance. This finding of partial impact of palmitoylation is reminiscent of the recent work on palmitoylation of the myosin light chain in Toxoplasma gondii (Rompikuntal et al, 2020), where disruption of palmitoylation led to the partial disassembly of the gliding motor complex but had little impact on motility itself. Considering the EM images showing large invaginations of the IMC away from the plasma membrane in concavin(-) sporozoites, we postulate that concavin might contribute towards riveting the plasma membrane to the subtending IMC, which are a constant distance of 25 nm apart.…”
Section: Discussionsupporting
confidence: 61%
“…The reactive cysteine identified in Tg ISPH contributes to an iron-sulfur cluster that is required for enzyme catalysis, and therefore any substitutions at this site are expected to be deleterious. Tg MLC1 is part of the glideosome complex required for parasite motility and host-cell invasion 31 and contains two N-terminal reactive cysteines that are known to be S -acylated 32,33 yet are non-essential for Tg MLC1 function 34 . We therefore hypothesized that substitutions at this site would not affect parasite fitness.…”
Section: Main Textmentioning
confidence: 99%
“…Likewise, the absence of GAP45 in gregarines and Cryptosporidium maybe compensated by other GAP-like proteins or even not be a problem at all; indeed, it has been proposed that a motor architecture could be organized in a much looser manner, in which actin-myosin motors push in a general backward direction, but without necessarily being guided by GAP proteins (Tardieux and Baum, 2016). Furthermore, while TgMLC1 binding to TgGAP45 is considered a key component of the parasite's force transduction mechanism, it has recently been shown that loss of TgMLC1 binding to TgGAP45 has little effect on their ability to initiate or maintain movement 102 , questioning again the real role of GAP45 and suggesting our comprehension of the glideosome's proteins' intrication is still incomplete.…”
Section: The Gregarine Glideosome(s)mentioning
confidence: 99%